(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Tobacco, which is a product of Nicotiana tabacum, has nicotine as its principal phytochemical. Nicotine has been reported to be an addictive drug and the leading cause of tobacco addiction worldwide with consequent renal implications. Therefore, this study was conducted to investigate the effect of the aqueous extract of Nicotiana. tabacum on serum electrolytes, urea and creatinine levels as indices of renal function in male rats. A total of 18 male wistar rats weighing 140-230g were used for this study. The animals were randomly divided into three groups (A, B and C), containing 6 rats each. Group A served as control while Group B and C were orally administered sublethal doses of 20 and 30 mg/kg body weight of the Nicotiana. tabacum extract respectively once per day for three weeks. At the end of the experimental period, all the animals were sacrificed. Blood samples were collected for biochemical assay. The results showed a significant increase (p<0.05) in the serum concentration of sodium, potassium and urea levels of rats treated with the extract when compared with the control. However, serum concentrations of chloride, bicarbonate and creatinine showed no significant appreciable differences between the treated groups and the control group (p<0.05). In conclusion, the study showed that aqueous extract of Nicotiana tabacum is associated with renal dysfunction with consequent hypernatremia and hyperkalemia, and may also suggest impaired urea clearance by the kidneys in male wistar rats.